Product variety and lead-time analysis in pc assembly industry using simulation technique / Nor Hayati Saad (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2006)
Product variety is one of the main market strategies in the mass customization (MC). The aim of MC is to satisfy individual needs with mass production efficiency. The diversification of product line is very important in today's business environment, where the customers are from various level of economic status, various ranges of age and have different need on certain product. In broadening product line based on customer requirement, it is analogous to increase relative attractions of the firm's product portfolio vis-a-vis competition. However, it may give negative effects on the manufacturing performance such as quality, cost, and problems in expediting customer orders. Hence, the main focus of this paper is to analyse the impact of product variety on lead-time. Lead- time is one of the very important performance indicators in measuring the performance of an organization. It is measured between placement of the order in the production until delivery time to customer. In analysing the impact, simulation model was built based on the focused manufacturing environment, in the area of Personal Computer (PC) Assembly Industry. The model was simulated using ARENA Simulation Software. Based on the quantitative result of the simulated model, the correlations between product variety and lead - time were analysed and observed.